Manipulasi Organ Golgi Tendon Untuk Mengurangi Tingkat Spastisitas Otot-Otot Penggerak Lengan Pasca Stroke Infark - Muhammad Mudatsir Syatibi; Suhardi Suhardi (Jurnal Keterapian Fisik, 2016)
Abstract: Manipulation, GTO, Spasticity. Stroke is a syndrome which is attacked rapidly and happening more than 24 hours and causing cerebral function problem. Stroke make someone get daily activity problem because of the spasticity. One of treatment to decrease the spasticity is Golgi Tendon Organ (GTO) manipulation which can reduce muscle’s tones that higher than normal. The aim of the study: is to knowing the effect of GTO manipulation in decreasing arm muscle spasticity for non haemorhagic stroke. Method: is two groups pre and post test design. Location and time research: is in Physical Therapy Unit of Dr. Moewardi Hospital Surakarta. Research Subject: are all of stroke patients in Dr. Moewardi Hospital who turned into inclusion and exclusion criteria, n=15 subject in I group and n= 14 subjects in II group. Analyze: Hipotesis test with non parametric test are Wilcoxon test dan Mann Whitnet test. Conclusion: (1) GTO manipulation can decrease arm muscle spasticity for right non haemorhagic stroke (p=0,000), (2) GTO manipulation can decrease arm muscle spasticity for left non haemorhagic stroke (p=0,001), and (3) no different effect of GTO manipulation to decrease arm muscle spasticity for non haemorhagic stroke between right and left side (p=0,353).